Infliximab Dose Reduction Sustains the Clinical Treatment Effect in Active HLAB27 Positive Ankylosing Spondylitis: A Two-Year Pilot Study. (5th September 2013) - Mörck, Boel; Pullerits, Rille; Geijer, Mats; Bremell, Tomas; Forsblad-d'Elia, Helena
Abstract : The rationale of the study was to evaluate the efficacy of infliximab (IFX) treatment in patients with ankylosing spondylitis (AS) and to determine whether IFX dose reduction and interval extension sustains the treatment effect. Nineteen patients were included and treated with IFX 5 mg/kg every 6 weeks for 56 weeks. All patients concomitantly received MTX with median dose 7.5 mg/weekly. During the second year, the IFX dose was reduced to 3 mg/kg every 8 weeks. Eighteen patients completed the 1-year and 15 patients the 2-year trial. The ≥50% improvement at week 16 from baseline of BASDAI was achieved in 16/19 (84%) patients. Significant reductions in BASDAI, BASFI, and BASMI scores, decrease in ESR and CRP, and improvement in SF-36 were observed at weeks 16 and 56. The MRI-defined inflammatory changes in the sacroiliac joints disappeared in 10/15 patients (67%) already at 16 weeks. IFX treatment effect was sustained throughout the second year after IFX dose reduction and interval extension. We conclude that IFX treatment is effective in well-established active AS and a dose reduction sustains the treatment effect. These observations are of clinical importance and open the opportunity to reduce the drug costs. This trial is registered with ClinicalTrials.gov NCT01850121.